Metabolic Value Chemoattractants Are Preferentially Recognized at Broad Ligand Range Chemoreceptor of Pseudomonas putida KT2440 - Fernández, Matilde; Matilla, Miguel A.; Ortega, Álvaro; Krell, Tino (Frontiers in Microbiology, 2017)
Bacteria have evolved a wide range of chemoreceptors with different ligand specificities. Typically, chemoreceptors bind ligands with elevated specificity and ligands serve as growth substrates. However, there is a chemoreceptor family that has a broad ligand specificity including many compounds that are not of metabolic value. To advance the understanding of this family, we have used the PcaY_PP (PP2643) chemoreceptor of Pseudomonas putida KT2440 as a model. Using Isothermal Titration Calorimetry we showed here that the recombinant ligand binding domain (LBD) of PcaY_PP recognizes 17 different C6-ring containing carboxylic acids with KD values between 3.7 and 138 µM and chemoeffector affinity correlated with the magnitude of the chemotactic response. Mutation of the pcaY_PP gene abolished chemotaxis to these compounds; phenotype that was restored following gene complementation. Growth experiments using PcaY_PP ligands as sole C-sources revealed functional relationships between their metabolic potential and affinity for the chemoreceptor. Thus, only 7 PcaY_PP ligands supported growth and their KD values correlated with the length of the bacterial lag phase. Furthermore, PcaY_PP ligands that did not support growth had significantly higher KD values than those that did. The receptor has thus binds preferentially compounds that serve as C-sources and amongst them those that rapidly promote growth. Tightest binding compounds were quinate, shikimate, 3-dehydroshikimate and protocatechuate, which are at the interception of the biosynthetic shikimate and catabolic quinate pathways. Analytical ultracentrifugation studies showed that ligand free PcaY_PP-LBD is present in a monomer-dimer equilibrium (KD= 57.5 µM). Ligand binding caused a complete shift to the dimeric state, which appears to be a general feature of four-helix bundle LBDs. This study indicates that the metabolic potential of compounds is an important parameter in the molecular recognition by broad ligand range chemoreceptors.